Clinical characteristics and outcomes of neonatal heart failure: a single-center retrospective analysis - Sihan Wang; Lili Ma; Liangliang Li; Xiangyun Yin; Ping Yang; Xianghong Li; Hongmin Xi (Frontiers in Pediatrics, 2026)
Background Neonatal heart failure (HF) is a severe condition associated with high mortality because of immature organ function and limited cardiovascular reserve. However, studies focusing specifically on HF in neonates remain limited. This study aimed to characterize the clinical features of neonatal HF and identify factors associated with mortality, with additional analyses according to etiology and gestational age. Methods This retrospective study included 89 neonates diagnosed with HF and admitted to our hospital between June 2016 and December 2025. Patients were classified into survival and death groups and were further stratified by etiology and gestational age (<34 weeks vs. ≥ 34 weeks). Logistic regression analyses were performed to identify factors associated with mortality, and model discrimination was evaluated using receiver operating characteristic (ROC) analysis. Results The overall mortality was 31.5%. The primary causes of HF were critical congenital heart disease (28%), severe arrhythmia (13%), pulmonary hypertension (12%), extremely severe anemia (12%), and perinatal asphyxia (10%). Compared with the survival group, the death group had lower birth weight, lower Apgar scores, higher N-terminal pro-brain natriuretic peptide (NT-proBNP) levels, lower left ventricular ejection fraction (LVEF), and higher rate of fetal distress, respiratory failure, and shock. Multivariable analysis showed that fetal distress (OR, 7.70) and oliguria (OR, 7.32) were associated with higher mortality, whereas higher LVEF (OR per 1% increase, 0.94) was associated with lower mortality. The combined model had an AUC of 0.806 (95% CI, 0.702–0.909). In subgroup analysis, neonates born at <34 weeks had higher NT-proBNP levels, longer durations of invasive and non-invasive mechanical ventilation, longer hospital stays, higher rates of fetal distress, bronchopulmonary dysplasia and anemia, greater use of pulmonary surfactant, and higher mortality than those born at ≥34 weeks. No significant interactions by gestational age were observed for fetal distress, oliguria, or LVEF. Conclusions Neonatal HF is associated with substantial mortality and is most commonly attributable to critical congenital heart disease, severe arrhythmia and other underlying conditions. Fetal distress and oliguria were independently associated with higher mortality, whereas higher LVEF was associated with lower mortality. Early recognition and targeted management are particularly important in preterm and other high-risk neonates.